“Sekolah untuk Masa Depan”, Membangun Pendidikan Karakter Anak Usia Sekolah yang Mandiri, Sehat dan Kreatif di Kota Pangkalpinang, Bangka - Tiara Elgifienda; Tiara Puspa Anjani; Dian Fitri K; Lili Liana; Ardiansyah Kurniawan (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
"School for the Future: Independent, Healthy, and Creative Integrative Character Education" is a community service activity that employs an interdisciplinary approach to integrate a variety of educational concepts that we believe are crucial for the education of school-age children. This Community Service activity is conducted through a variety of activities, such as the fun learning through a bilingual approach with elementary school materials, the play of snakes and ladders, and Fish Eating Campaign (Gemarikan) to elementary school students, and the evaluation of materials. Many parties are involved in this activity, and there is still room for development in order to facilitate the implementation of similar activities. However, the community service team feels the need to consider carrying out similar activities with a continuation scheme in the following year to facilitate measuring the effectiveness and impact of this activity on students. Nevertheless, in order to increase students' enthusiasm for the activity, it is necessary to develop more innovative and inventive game designs.